Structure, electronic properties, NBO, NLO and chemi-cal reactivity of bis (1, 4-dithiafulvalene) derivatives: functional density theory study - Abbaz, Tahar; Bendjeddou, Amel; Villemin, Didier (International Journal of Advanced Chemistry, 2017)
In this work, through computational study based on density functional theory (DFT/B3LYP) using basis set 6-31G (d,p) a number of global and local reactivity descriptors for a series of molecules containing a TTF function which are bis (1,4-dithiafulvalene) derivatives. They were computed to predict the reactivity and the reactive sites on the molecules. The molecular geometry and the electronic properties in the ground state such as frontier molecular orbital (HOMO and LUMO), ionization potential (I) and electron affinity (A) were investigated to get a better insight of the molecular properties. Molecular electrostatic potential (MEP) for all compounds were determined to check their electrophilic or nucleophilic reactivity. Fukui index, polarizability, hyperpolarizability, second order NLO property and natural bond orbital (NBO) analyses have also employed to determine the reactivity of bis (1,4-dithiafulvalene) derivatives.